Exploring place attachment - Assaker, Guy (2017)
A study was conducted to develop a scale to measure place attachment at sports venues. A total of sixty-five questionnaire responses were analysed using exploratory factor analysis to test the validity of a four factor structure. Sixteen items were used to measure emotional engagement, place identity, place dependence and place symbolism. It was found necessary to amend the initial measures for place dependence and to focus on spectator evaluations of their event experience rather than the functionality of venues for competitors. The study was completed at two events in Adelaide, South Australia. Opportunities to use the scale at different types of events and to examine relationships between place attachments and other factors influencing the event experience are discussed.